LC-MS Profiling of Kakkonto and Identification of Ephedrine as a Key Component for Its Anti-Glycation Activity - Ito, Kaori; Kikuchi, Takashi; Ikube, Kanako; Otsuki, Kouharu; Koike, Kazuo; Li, Wei (Molecules, 2023)
A total of 147 oral Kampo prescriptions, which are used clinically in Japan, were evaluated for their anti-glycation activity. Kakkonto demonstrated significant anti-glycation activity, prompting further analysis of its chemical constituents using LC-MS, which revealed the presence of two alkaloids, fourteen flavonoids, two but-2-enolides, five monoterpenoids, and four triterpenoid glycosides. To identify the components responsible for its anti-glycation activity, the Kakkonto extract was reacted with glyceraldehyde (GA) or methylglyoxal (MGO) and analyzed using LC-MS. In LC-MS analysis of Kakkonto reacted with GA, the peak intensity of ephedrine was attenuated, and three products from ephedrine-scavenging GA were detected. Similarly, LC-MS analysis of Kakkonto reacted with MGO revealed two products from ephedrine reacting with MGO. These results indicated that ephedrine was responsible for the observed anti-glycation activity of Kakkonto. Ephedrae herba extract, which contains ephedrine, also showed strong anti-glycation activity, further supporting ephedrine’s contribution to Kakkonto’s reactive carbonyl species’ scavenging ability and anti-glycation activity.